First Report of Acetyl-CoA Carboxylase–Resistant Southern Crabgrass (Digitaria ciliaris) in the United States. (3rd April 2017) - Yu, Jialin; McCullough, Patrick E.; Czarnota, Mark A.
Abstract : Two populations of southern crabgrass identified in Georgia turfgrass were suspected to be resistant to sethoxydim. The objectives of this research were to evaluate the resistance levels of these biotypes to acetyl-CoA carboxylase (ACCase) inhibitors and alternative herbicides for control. From dose response experiments, the sethoxydim rate required to reduce shoot biomass 50% from the nontreated measured >64-times greater for both resistant (R) biotypes compared to the susceptible (S) biotype. Both R biotypes were cross-resistant to fenoxaprop and fluazifop. Clethodim at 290 gaiha −1 reduced dry shoot biomass of the R biotypes and the S biotype to 47 and 21% of the nontreated, respectively. The R biotypes were equally susceptible to MSMA at 2240 g ai ha −1, quinclorac at 840 g ai ha −1, and topramezone at 37 g ai ha −1 as compared to the S biotype. Sethoxydim at 315 and 945 g ha −1 provided <20% control of the southern crabgrass populations in four field experiments. However, clethodim and topramezone provided 83% and 76% control at 4 wks after treatment, respectively. These southern crabgrass biotypes are resistant to sethoxydim and aryloxyphenoxypropionate herbicides. Although the R biotypes were less susceptible to clethodim than the S biotype, treatments provided acceptable control in the field. This is the first report of ACCase-resistant southern crabgrass in the United States. Abstract : Dos poblaciones de Digitaria ciliaris fueron identificadas en céspedes en Georgia y se sospechó que podían ser resistentes a sethoxydim. Los objetivos de esta investigación fueron evaluar el nivel de resistencia de estos biotipos a herbicidas inhibidores de acetyl-CoA carboxylase (ACCase) y a herbicidas alternativos para su control. Con base en experimentos de respuesta a dosis, la dosis de sethoxydim requerida para reducir la biomasa de la parte aérea de la planta en 50% en comparación con el testigo sin tratamiento fue >64 veces mayor en ambos biotipos resistentes (R) al compararse con el biotipo susceptible (S). Ambos biotipos R tuvieron resistencia cruzada a fenoxaprop y fluazifop. Clethodim a 390 g ai ha −1 redujo la biomasa seca de la parte aérea de los biotipos R y del biotipo S a 47 y 21% del testigo sin tratamiento, respectivamente. Los biotipos R fueron igualmente susceptibles que el biotipo S a MSMA a 2240 g ai ha −1, quinclorac a 840 g ai ha −1, y topramezone a 37 g ai ha −1 . Sethoxydim a 315 y 945 g ha −1 brindó <20% de control de poblaciones de D. ciliaris en cuatro experimentos de campo. Sin embargo, clethodim y topramezone brindaron 83 y 76% de control a 4 semanas después del tratamiento, respectivamente. Estos biotipos de D. ciliaris son resistentes a sethoxydim y herbicidas aryloxyphenoxypropionate. Aunque los biotipos R fueron menos susceptibles a clethodim que el biotipo S, los tratamientos con este herbicida brindaron un control aceptable en campo. Este es el primer reporte de D. ciliaris resistente a ACCase en los Estados Unidos.